„Meat Should Be Prescribed in Very Small Doses, Arsenic-like”. How Josephine Joteyko and Varia Kipiani Pioneered Medical Research to Improve Vegetarianism in 1906: « Il faut prescrire l’usage de la viande en petite quantité, comme on prescrit l’arsenic » Josephine Joteyko et Varia Kipiani: la recherche médicale pionnière en faveur du végétarisme en 1906 - Joteyko, Josephine; Kipiani, Varia; Nowak, Ewa; Löwy, Ilana (ETHICS IN PROGRESS, 2020)
This compilation is based on the original report on a clinical survey conducted in Brussels (1905-1906) by Josephine Joteyko and Varia Kipiani with 43 vegetarians. Having advanced expertise in physiology and experimentalism, Joteyko (with Lithuanian and Polish origins) and Kipiani (with Georgian origins) discussed their findings at the Congress of the Belgian Society for Vegetarianism in 1906. For both children and adults, females and males, regardless of age, the findings demonstrated vegetarian dietary habits to be beneficiary for human development, the subjects’ physical and mental health, welfare, and physical and intellectual efficiency. Surprisingly, Joteyko and Kipiani confirmed C. Darwin’s observation across various nutritional cultures that vegetarian food would increase the energetic balance of the human body. Additionally, their focus on the moteur humain shows affinities with Taylorism, the modernist utopias of labor, the enhancement of human faculties, the protection of workers and their rights from automation, and applied social science represented by Joteyko and Kipiani as multidisciplinary investigators. The compilation was made on: J. Joteyko & V. Kipiani, Enquête scientifique sur les Végétariens de Bruxelles, Conférence donnée à la Société végétarienne de Belgique, le 4 décembre 1906, pp. 1–77, with no further correction.